2015
DOI: 10.1111/jne.12258
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Expression of Oestrogen Receptor α and Androgen Receptor is Sex‐, Age‐ and Region‐Dependent in Mice

Abstract: Sex steroid hormones act on developing neural circuits regulating the hypothalamic-pituitary-gonadal axis and are involved in hormone-sensitive behaviours. These hormones act mainly via nuclear receptors, such as oestrogen receptor (ER)-α and androgen receptor (AR). By using immunohistochemistry, we analysed the expression level of ERα and AR throughout perinatal life [at embryonic (E) day 19 and postnatal (P) days 5, 15 and 25] and in adulthood in several hypothalamic nuclei controlling reproduction in both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 70 publications
10
61
0
3
Order By: Relevance
“…The total amount of immunoreactivity (ir) for each receptor was analyzed as previously described (Brock et al, 2010;2015) Briefly, one representative section was selected for several brain nuclei and was digitized using a video camera (CFW 1612C; Scion Corp., Frederick, MD, USA) attached to a microscope (MTV-3, x 20 objective; Olympus, Tokyo, Japan). Then, immunoreactivity was quantified with a computer-based image analysis system using the particle-counting protocol of NIH IMAGE, version 1.49® (Wayne Rasband, NIH,…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of immunoreactivity (ir) for each receptor was analyzed as previously described (Brock et al, 2010;2015) Briefly, one representative section was selected for several brain nuclei and was digitized using a video camera (CFW 1612C; Scion Corp., Frederick, MD, USA) attached to a microscope (MTV-3, x 20 objective; Olympus, Tokyo, Japan). Then, immunoreactivity was quantified with a computer-based image analysis system using the particle-counting protocol of NIH IMAGE, version 1.49® (Wayne Rasband, NIH,…”
Section: Discussionmentioning
confidence: 99%
“…The classical, estrogen receptor 1(ER-alpha; Simerly et al, 1990; Merchenthaler et al, 2004), the novel subtype, estrogen receptor 2 (ER-beta; Shughrue et al, 1997; Merchenthaler et al, 2004; Zuloaga et al, 2014) and the membrane-associated form GPER1 (Treen et al, 2016) have all been identified and mapped in different structural compartments of the region. Signaling to the region by progesterone and androgen hormones has also been demonstrated and the cellular distribution of their receptors elucidated (Handa et al, 1986; Simerly et al, 1990; Kanaya et al, 2014; Brock et al, 2015). The KP/GABA/glutamate neurons of the region are exceptional targets of gonadal hormones, including E2.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the SDN MPOA, AVPV is larger in females than in males [79,80]. In AVPV, the sex difference was described in the number of cells expressing alpha and β oestrogen receptors, with females having more immunopositive cells for both receptors [81][82][83][84], and tyrosine hydroxylase, a marker for dopaminergic cells, which are also present in higher numbers in female AVPV [85,86]. Sex differences were also observed in the expression of kisspeptin, a regulator of GnRH secretion essential for the onset of puberty.…”
Section: Organizational Hormonal Effects On Structural Differences Inmentioning
confidence: 90%